Revision of the genus Apterodela Rivalier, 1950 (Coleoptera, Cicindelidae) - Matalin, Andrey V.; Wiesner, Jürgen; Xiong, Xinxin; Araki, Takashi (Zootaxa, 2024)
A revision of the genus Apterodela Rivalier, 1950 is presented. The new subgenus Protoapterodela subgen. nov. with Apterodela shirakii (W. Horn, 1927) as its type species is established. The lectotype and the paralectotype of Cicindela ovipennis Bates, 1883 and Cicindela shirakii W. Horn, 1927 as well as the neotype of Cicindela lobipennis Bates, 1888 are designated. Apterodela (s. str.) bivirgulata (Fairmaire, 1889), stat. rest. is extracted from the synonym of Apterodela (s. str.) lobipennis (Bates, 1888) and is considered as a separate species. Two new species and one new subspecies from China are described as well: Apterodela (s. str.) alopecomma sp. nov.—from Sichuan Province, Apterodela (s. str.) latissima sp. nov.—from Yunnan Province, and Apterodela (s. str.) bivirgulata occidentalis ssp. nov.—from Qinghai, Gansu, Shaanxi, Henan, Shanxi, Sichuan Provinces, and Inner Mongolia Autonomus Region. A key to identifying the species of the genus Apterodela is provided, and its taxonomic status is examined.